THE EDUCATION BY PRACTICE - THE MULTIMEDIA PROJECT AS A PARTICIPATION OF STUDENT AND TEACHER - BARTOŠ, David (Trends in education, 2019)
Almost every day we can hear both from professional pedagogic circles and from general public louder and louder comments on the necessity of school reformation or the activation of education, so it would better reflect the needs of current society and life-style, its demands, processes, characteristics and development. All of this is heading towards actualization of key competences, forms and contents of education, that are connected mainly to interdisciplinarity, communication skills, cooperation and ability to present one's own skills, knowledge and experience. These tendencies are happening in the world where digital technology is widespread and multimedia are available for almost every person, even from a very young age. This article analyzes and describes both of the above mentioned issues and offers a suitable use of their synthesis in edication.
Keywords: multimedia project; interdisciplinarity; equeality; participation